Improved conversion, selectivity, and stability during CO2 methanation by the incorporation of Ce in Ni, Co, and Fe-hydrotalcite-derived catalysts (2024)
ABSTRACT: In this work, Ni-based mixed metal oxide (MMOs) materials were synthesized by coprecipitation, and then ceria (CeO2) was incorporated. The obtained structures were characterized by XRD, TEM, BET, H2-TPR, and CO2-TPD techniques. The synthesized materials were evaluated in the CO2 methanation process (250–400 ◦C range). Firstly, the effects of space velocity and Ni loading on the catalyst were tested, and 36000 h− 1 and 5 % of Ni were found to be suitable conditions for CO2 conversion. The addition of Co or Fe to the Ni-based MMO was then assessed. Co improved the catalytic activity, meanwhile, the Fe addition did not have an enhancing effect. Afterward, the role of CeO2 as support on Ni-, NiFe- and NiCo-based MMOs was evaluated, evidencing that selectivity and space-time yields were enhanced in the materials by the CeO2 presence. Furthermore, due to the characteristics of CeO2, the MMO containing nickel, cobalt, and ceria was more stable, showing ~85% conversion of CO2 after 1400 min of continuous use.